2020
DOI: 10.3390/jcm9061671
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Related Clinical Characteristics and Myocardial Fibrosis and Their Association with Prognosis in Hypertrophic Cardiomyopathy

Abstract: Background: The spectrum of genetic variants and their clinical significance of Hypertrophic cardiomyopathy (HCM) have been poorly studied in Asian patients. The objectives of this study were to assess the spectrum of genetic variants and genotype–phenotype relationships within a Korean HCM population. Methods: Eighty-nine consecutive unrelated HCM patients were included. All patients underwent genotypic analysis for 23 HCM-associated genes. Clinical parameters including echocardiographic and cardiac magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…The proband's two daughters had familial HCM, which suggested that idiopathic RCM might be a different phenotype than familial HCM. Similar to the phenotype of the proband's two daughters, this frameshift mutation has been previously reported to be related to Korean HCM [11]. An intriguing aspect of sarcomere protein mutations is pleiotropy.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The proband's two daughters had familial HCM, which suggested that idiopathic RCM might be a different phenotype than familial HCM. Similar to the phenotype of the proband's two daughters, this frameshift mutation has been previously reported to be related to Korean HCM [11]. An intriguing aspect of sarcomere protein mutations is pleiotropy.…”
Section: Discussionsupporting
confidence: 74%
“…Significantly, the mechanisms underlying the phenotypic diversity of cardiomyopathy caused by mutations in the same genes and the basis for the variable expressivity of cardiomyopathy phenotypes within family members are poorly understood [ 8 , 9 ]. To date, substantial advances in the understanding of the genetic causes of cardiomyopathies have become feasible because of the development of high-throughput approaches to DNA sequencing, namely, massively parallel sequencing (MPS) [ 10 , 11 ]. Furthermore, restrictive ventricular physiology, which is known to be one of the distinct hemodynamic characteristics of RCM, can be observed in HCM [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…When tissue is subjected to sustained injury, the substantial chronic injury could lead to uncontrolled myofibroblast activation and excessive accumulation of ECM, which results in a chronic inflammatory environment infiltrated by macrophages, lymphocytes, eosinophils, and other immune cells [ 43 ]. In addition, genetic changes in organs also participate in the progress of fibrosis, such as Mucin 5B (MUC5B) in pulmonary fibrosis and Myosin Heavy Chain 7 in cardiac fibrosis [ 44 , 45 ]. These specific mutations associated with fibrosis suggest that some non-fibroblast types are involved upstream of the pathogenesis of fibrosis, highlighting the importance of multicellular interactions in this disease.…”
Section: Fibrotic Diseases: Pathogenesis and Mechanismmentioning
confidence: 99%
“…Collagen-binding Integrins such as α1β1, α2β1, and α11β1 have been found to contribute to fibroblast function in wound healing [ 43 , 44 ]. The α1β1 Integrins expressed in fibroblasts can bind with collagens and mediate ECM accumulation during wound repairing [ 45 , 46 ]. The type I collagen-binding α2β1 Integrins can promote myofibroblast differentiation and accelerate wound closure [ 46 , 47 ].…”
Section: Fibrotic Diseases: Pathogenesis and Mechanismmentioning
confidence: 99%
“…99 Finally, some genetic mutations have been found to be associated with fibrosis. For example, mutations in telomerase reverse transcriptase (TERT) and mucin 5B (MUC5B) are associated with pulmonary fibrosis, [100][101][102][103] while mutations in the myh7 gene is associated with cardiac fibrosis, 104 and mutation in dystrophin (DMD) is associated with Duchenne muscular dystrophy-associated skeletal muscle fibrosis. 105…”
Section: Fibrosismentioning
confidence: 99%